Congolese Plantation Workers Art League - Roelandt, Els; Barois De Cavel, Eva; Vergès, Françoise; Koster, Jaap; Malaquez, Dominique; Katrib, Ruba; Martens, Renzo (Berlin : Sternberg press, 2016)
Martens, Renzo, Mingiedi, Mega; Pongo, Leonard ; Helio, Eleonore; Ikeba, Michel ; Tamasala, Cédrick
Congo, postkolonialisme, plantage arbeid, chocolade sculpturen, Lusanga, palmolie, CATPC
boek
Keywords: Martens, Renzo